An Unusual Presentation of Kawasaki Disease: Gallbladder Hydrops and Acute Cholestatic Hepatitis - B. O. Kılıç; Ş. Baysun; T. C. Gökşen; İ. Akınbingöl; Z. Arslan (Case Reports in Medicine)
Kawasaki disease is the most common vasculitis of childhood. In its classical form, at least four of five diagnostic criteria including cervical lymphadenopathy (1.5 cm or more), nonsuppurative conjunctivitis, intraoral mucosal changes, edema in hands and feet, and maculopapular rash are required with prolonged fever over 5 days. Atypical cases which are different from the classical type or incomplete cases which does not include all the diagnostic criteria can be seen. The typical Kawasaki disease is a self-limiting disease with fever lasting for an average of two weeks. In such patients who have not been diagnosed and whose treatment has been delayed, coronary artery aneurysm, myocardial depression, arrhythmia, and vascular complications may increase morbidity and mortality. We would like to present a rare case of an atypical patient with gallbladder hydrops and acute cholestatic hepatitis.